Enhancing the Retention of Therapeutic Cells Using Novel Biomaterials - Dutcher, Megan (Université d'Ottawa / University of Ottawa, 2022)
Cell-based therapeutic strategies are becoming increasingly popular in treating many diseases that historically have been challenging to treat. Strategies involving injections of healthy cells into damaged tissues have benefits over current transplantation and drug strategies because they eliminate the need for long term use of immunosuppressing drugs and reduce the issues of limited availabilities of tissue donors. However, there are still major issues with current cell-based strategies, including limited cell engraftment and retention at the site of injury. Recent studies show that a very limited number of cells are retained at the site of injection, but therapeutic effects as still observed. Examples include improved cardiac function when cells are used to treat myocardial infarctions, improvements are observed for treating retinal degenerative diseases, and increased bone formation in bone regeneration strategies, as well as improvements for many other disease treatments. Encapsulating cells in hydrogel microcapsules has been shown to increase cell retention significantly, as well as protect the cells from any unwanted, negative immune responses from the host. However, previous studies showed that long-term retention of encapsulated cells is still reduced due to cell escape or egress from the hydrogel microcapsules. Once escaped, these cells are free floating, and surrounding vasculature and blood flow clear the cells from the site quickly. The proposed strategy of reducing cellular clearance is through modifying the encapsulation material with cell binding domains, specifically by adding a peptide sequence of arginine, glycine, and aspartate (RGD). These binding sites allow the cells to adhere to the outside of the microcapsules after they have escaped. Attachment to the microcapsules means the egressed cells are not free floating and therefore will not be cleared away from the site of injury as easily, therefore leading to long-term retention at the site of injury. Long-term retention is believed to increase efficacy of these cell-based treatments. Cellular attachment to hydrogel microcapsules was investigated by encapsulating cells in regular agarose and in RGD-modified agarose. Encapsulation was conducted using a microfluidic device to create uniform, monodisperse agarose microcapsules containing cells. These encapsulated cells were then studied using timepoint fluorescence microscopy to determine cell viability, microcapsule occupancy, cell escape from microcapsules and cellular adhesion onto the microcapsules. These quantities were assessed at three timepoints after encapsulation - 2 h, 24 h, and 48 h - to investigate whether cell behaviour was changing with time. Different environmental conditions were investigated as well, to imitate different cellular environments that may affect cell adhesion to a material. Samples were studied in cell culture treated dishes as well as poly(2-hydroxyethyl methacrylate) (pHEMA) coated dishes to simulate environments in which cells can adhere to surrounding surfaces, and environments in which adhesion is inhibited. The results presented here show that RGD-modified encapsulation material does increase cell attachment to the outside of microcapsules. I show that this cellular behaviour occurs with multiple cell types, including therapeutically relevant cells such as explant derived cardiac stem cells, and human umbilical vein endothelial cells. Cells behave quite differently in regular, unmodified agarose, where almost no cell attachment is observed. I show that this novel biomaterial does not negatively impact viability of encapsulated cells, and can be used inside semi-automated, scalable microfluidic devices for cell encapsulation. The research presented here shows promise for eliminating some of the limitations currently observed in many cell-based therapeutic strategies and it is hypothesized that the use of this novel biomaterial for cell encapsulation will lead to increased therapeutic effects in vivo due to increasing cellular retention at the site of injury.
Keywords: biophysics; biomaterials